Konsep Pendidikan YB. Mangunwijaya. Pr. - Aly Masyhar (Tribakti: Jurnal Pemikiran Keislaman, 2009)
Education is very important for human. Even, it includes in Human Right Point. But, education in our country has got many critical from education criticists. According to them, the education of our country, especially it’s system, administrative, and curriculum, has been very broken. It couldn’t make it’s students clever and understand with their social and habit conditions. About it, Agus Sunyoto, a historian and education criticist from Malang, said that our education just make it’s students the illusionists, because our education just teachs some lessons that are far from the fact. Romo Mangun’s education concept covers about education philosophy – epistemology, ontology, and axiology-, and than learning methods, curriculum, and society relation between education and it’s society. His education concept was influenced by west education criticists, as like Paulo Friere, Ivan Illich, Jurgen Habermas, Foucoult, Jean Pieget and others, but he could sift and couple with values of Indonesian culture. And one thing, that has to been noted, is that all of his concepts always are rested on religious values. So, someone doesn’t get wrong if he called that Mangun’s concept is education concept based on freedom and religious, because in the fact it is right.